2008 Chinese Milk Products Crisis - Rini Ariani Basyamfar (Rona Teknik Pertanian, 2014)
Abstract. Milk is one of the most important food products for children’s growth and overall health.  Melamine (2,4,6-triazine-1,3,5-triamino) is an organic compound used in the manufacture of pesticides, plastics, sanitizers, and disinfectants.  Melamine when added to milk increases the overall amount of nitrogen in the milk thus fooling common tests for protein content.  Melamine is also extremely harmful when ingested, especially for young children.  Sanlu, one of China's largest dairy producers, diluted their milk products with water and added then added melamine to fool the protein tests. Consumption of milk containing melamine in amounts greater than 1 mg/kg can cause kidney failure, bladder cancer and death.  Testing milk using the LC-MS/MS and GC-MS/MS methods can reveal melamine contamination. Further actions that can be implemented to reduce milk adulteration include product traceability, corporate transparency, 100% product testing procedures and consistent enforcement of the law. 2008 Krisis Produk Susu ChinaAbstrak. Susu merupakan salah satu produk pangan yang paling penting untuk pertumbuhan anak-anak dan kesehatan. Melamin (2,4,6-triazina-1,3,5-triamino) adalah senyawa organik yang digunakan dalam pembuatan pestisida, plastik, pembersih, dan disinfektan. Melamin ketika ditambahkan ke susu meningkatkan jumlah keseluruhan nitrogen dalam susu sehingga mengelabui tes umum untuk kandungan protein. Melamin juga sangat berbahaya bila tertelan, terutama untuk anak-anak. Sanlu, salah satu produsen susu terbesar di China, mengencerkan produk susu mereka dengan air dan menambahkan melamin untuk mengelabui tes protein. Konsumsi susu yang mengandung melamin dalam jumlah yang lebih besar dari 1 mg/kg dapat menyebabkan gagal ginjal, kanker kandung kemih dan kematian. Pengujian susu menggunakan LC-MS/MS dan metode GC-MS/MS dapat mengungkapkan kontaminasi melamin. Tindakan lebih lanjut yang dapat diterapkan untuk mengurangi pemalsuan susu antara lain penelusuran produk, transparansi perusahaan, 100% prosedur pengujian produk dan penegakan hukum yang konsisten.